2018
DOI: 10.1017/s0714980818000090
|View full text |Cite
|
Sign up to set email alerts
|

Later-Life Homelessness as Disenfranchised Grief

Abstract: Although interest on older homelessness is gaining momentum, little research has considered the experiences of first-time homelessness from the perspective of older adults themselves. This constructivist grounded-theory study addresses this gap by exploring how societal perceptions of homelessness and aging shape access to housing, services, and perceptions of self for 15 older adults residing in emergency homeless shelters in Montreal, (Quebec, Canada). Findings revealed that homelessness evoked a grief respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…Changes to the homeless population continue today: a troubling trend identified recently has been a 58 per cent increase in the number of seniors experiencing homelessness for the first time over the 2005-14 period (ESDC 2017). 18 This confirms what many researchers have long argued -that the population of people experiencing homelessness is aging in tandem with the Canadian population as a whole (Burns, Sussman, and Bourgeois-Guérin 2018). At the same time, service providers and policy-makers have found that more trans people are experiencing homelessness and that this group is particularly vulnerable, requiring specialized and safe spaces.…”
Section: Who Experiences Homelessness?supporting
confidence: 67%
“…Changes to the homeless population continue today: a troubling trend identified recently has been a 58 per cent increase in the number of seniors experiencing homelessness for the first time over the 2005-14 period (ESDC 2017). 18 This confirms what many researchers have long argued -that the population of people experiencing homelessness is aging in tandem with the Canadian population as a whole (Burns, Sussman, and Bourgeois-Guérin 2018). At the same time, service providers and policy-makers have found that more trans people are experiencing homelessness and that this group is particularly vulnerable, requiring specialized and safe spaces.…”
Section: Who Experiences Homelessness?supporting
confidence: 67%
“…However, literature on grief and bereavement poses some incongruences regarding what types of loss could trigger a grieving process or psychopathologies. Some studies show that non-social loss (e.g., loss of house, job, or health) can trigger a maladaptive grieving process [ 21 , 22 , 23 , 24 , 25 ]. Nevertheless, other studies have failed to find a statistical significance linked to it [ 26 ].…”
Section: Introductionmentioning
confidence: 99%